Socio-demographic and Clinical Characteristic of Women Availing Pap Smear Services in Samtse District, Bhutan - Dorji, Thinley; Pokhrel, Hari Prasad; Tshokey, Tshokey (Asian Pacific Journal of Cancer Biology, 2020)
Background: The case burden of cervical cancer has been increasing globally especially in developing countries without proper health system. Cervical cancer can be eliminated with timely vaccination and screening program as it usually takes years for pre-malignant lesions to develop into malignant lesion. Bhutan has committed to eliminate cervical cancer. Thus, it is important to understand the factors associated with abnormal Pap test findings. Methodology: A retrospective study was conducted using the Pap smear data for the year 2018. It was extracted from the records maintained in the cytology unit of Samtse General Hospital. Result: The abnormal slide rate in this study was 2.5%. The majority of women seeking Pap smear services were women in reproductive age group and housewife by occupation. There were significant differences between age groups and marital status among normal in the Pap test results. Conclusion: The slide abnormality of Pap smear in Samtse District is low. The abnormality is more common among married and older women. Therefore, additional screening efforts needs to be put into this group to detect pre-malignant lesions.